Reflective Assistance in Internalizing Isra Mi'raj Values for Strengthening the Character of Elementary School Students - Ali Ridho; Siti Rahmah; Nor Lila Sari (TAAWUN, 2025)
This community service activity aimed to instill a deep understanding of the spiritual and moral values associated with the Isra Mi’raj event of Prophet Muhammad among elementary school students through an educational support program. The program was conducted at SDN Gambut 3, involving fourth, fifth, and sixth-grade students as the primary participants. The methods employed included educational lectures, storytelling, interactive discussions, and reflective sessions on Islamic values relevant to the students' daily lives. The activity began with an exploration of the students’ prior knowledge about Isra Mi’raj, followed by the delivery of materials communicatively and contextually, and concluded with both personal and class-wide reflection sessions. The results of the activity showed an improvement in students' understanding of exemplary values, such as honesty, discipline in worship, and humility. Student responses reflected high enthusiasm throughout the reflective learning process. Furthermore, this activity had a positive impact on the school community by enriching the practical implementation of Islamic values in the school environment. The benefits of this program were evident in the increased student participation in school religious activities and positive changes in their daily attitudes, both at home and within the surrounding community.